ITC information system: a web-based information management framework for international technology commons - Wang, Wenbo (Kansas State University, 2016)
As a laboratory associated the English Language Program (ELP) at Kansas State University, the International Technology Commons (ITC) provides English instructions to students who are qualified to begin university work but do not meet the English proficiency standards for the university by using cutting-edge pedagogical technologies. The ITC Information System is a centralized web-based framework that manages the polices, processes, and procedures to make sure that the ITC can fulfill all tasks required to archive its objectives, including checking in/out electronic devices and/or books to students and faculties, registering new students during the enrollment, keeping track of ITC properties and assets, etc. As a full-stack project, the ITC Information System has been designed and implemented by utilizing multiple modern programming languages, frameworks, and platforms. Been serving the ITC since August 2015, the ITC Information System has significantly improved the efficiency of ITC electronic resources, and reduced the man-hours devoting to administrating undergraduate lab monitors. Leadership of the ELP appreciates the outcome and expresses expectation to broaden the scale of this project to serving more instructional divisions.
Keywords: Information system; International Technology Commons; PHP; Bootstrap